'A Play within a Play’: Why Hockney Still Matters at 80. A Review of the David Hockney Exhibition at the Tate Britain - Emilia Halton-Hernandez (Janeway JS, 2018)
This is a review of the recent Hockney retrospective held at the Tate Britain in London.